Application of Learning Technology in Domino Card Games on a large scale and individually to the responses of senior high school students - Mohammad Furqon HN; Madlazim Madlazim; Zainul Arifin Imam Supardi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Learning by applying game technology in learning media will attract students' attention. This study uses a domino physics game with quantities and units as materials. Each card will be printed with a barcode containing information regarding the principal amount, unit, symbol, and dimensions. The process of making physics domino card media uses the ADDIE development model. The trial was conducted on 133 class X students at one of the SHS in the Pamekasan and Surabaya Regencies. The results of the validation of the physics domino cards in the media aspect obtained a very valid average category value, and the material aspects got a very valid average category value. The results of the average percentage of responses of Al Amien Pamekasan senior high school students after using the domino physics media with indicators of ease of obtaining, interest, and usefulness obtained scores in the very good category. The results of the average percentage of responses from Pamekasan 4 senior high school students after using the domino physics media with indicators of ease of obtaining, interest, and usefulness obtained scores in the very good category. The average percentage of senior high school 9 Surabaya responses after using the domino physics media with indicators of ease of obtaining, interest, and usefulness received scores in the very good category. Domino physics learning media can make it easier for students to understand the material in quantities and units and instill a strong will to learn physics.